Validated thoracic vertebrae and costovertebral joints increase biofidelity of a human body model in hub impacts. (25th November 2019) - Aira, Jazmine; Guleyupoglu, Berkan; Jones, Derek; Koya, Bharath; Davis, Matthew; Gayzik, F. Scott
Abstract: Objective: A recent emphasis on nontraditional seating and omnidirectional impact directions has motivated the need for deformable representation of the thoracic spine (T-spine) in human body models. The goal of this study was to develop and validate a deformable T-spine for the Global Human Body Models Consortium (GHBMC) M50-O (average male occupant) human model and to demonstrate improved biofidelity. Methods: Eleven functional spinal units (FSUs) were developed with deformable vertebrae (cortical and trabecular), spinal and costovertebral ligaments, and intervertebral discs. Material properties for all parts were obtained from the literature. FSUs were subjected to quasistatic loads per Panjabi et al. (1976 ) in 6 degrees of freedom. Stiffness values were calculated for each moment (Nm/°) and translational force (N/µm). Updated costovertebral (CV) joints of ribs 2, 6, and 10 were subjected to moments along 3 axes per Duprey et al. (2010 ). The response was optimized by maximum force and laxity in the ligaments. In both cases, updated models were compared to the baseline approach, which employed rigid bodies and joint-like behavior. The deformable T-spine and CV joints were integrated into the full M50-O model Ver. 5.0β and 2 full-body cases were run: (1) a rear pendulum impact per Forman et al. (2015 ) at speeds up to 5.5 m/s. and (2) a lateral shoulder impact per Koh (2005 ) at 4.5 m/s. Quantitative evaluation protocols were used to evaluate the time history response vs. experimental data, with an average correlation and analysis (CORA) score of 0.76. Results: All FSU responses showed reduced stiffness vs. baseline. Tension, extension, torsion, and lateral bending became more compliant than experimental data. Like the experimental results, no trend was observed for joint response by level. CV joints showed good biofidelity. The response at ribs 2, 6, and 10 generally followed the experimental data. Conclusions: Deformable T-spine and CV joint validation has not been previously published and yielded high biofidelity in rear impact and notable improvement in lateral impact at the full body level. Future work will focus on localized T-spine injury criteria made possible by the introduction of this fully deformable representation of the anatomy.